The body and the word: at the intersection of religion and rape culture within church as a site of education and social formation - Lyter Bright, Laurie, author; Jennings, Louise, advisor; Souza, Caridad, committee member; Aragon, Antonette, committee member; Anderson, Sharon, committee member (Colorado State University. Libraries, 2021)
The work of this dissertation is to name and understand the intersection of religion and rape culture in the context of Christianity through understanding churches as sites of education and social formation. My positionality as researcher is shaped by my identity as a clergyperson and an activist in addressing gender-based violence. While those aspects of my identity frequently overlap, my roles as a clergy member and as an advocate for survivors of rape culture feel too often like living in parallel worlds. The overlap of these identities seemed readily apparent to me, yet I was not hearing rape culture discussed by other clergy, nor was the church providing space or meaningful support in the fight against gender-based violence. The perceived gap is where this research began. These two facets of my experience and identity cemented in me a desire to understand the intersection of faith and the lived realities of sexual violence. I interviewed scholars, preachers, and authors contributing to the discourse of the #metoo movement and who work to bridge the space between scripture, ritual, and community praxis. Participants are leaders in the focused and growing movement of addressing rape culture in theological scholarship and church teaching and preaching. Through semi-structured interviews, I sought understanding of three key lines of inquiry centering on the reasons and paths by which rape culture and church both intersect and interact. Through modified constructivist grounded theory analysis of these interviews, I determined that the church is indeed a contributor in the co-creation of rape culture. The duality of this conclusion is that the church already possesses the pedagogical pathways necessary to serve as a site of disruptive education in rape culture instead.
Keywords: gender; rape culture; social formation; gender-based violence; church; religion